Simulações hidrológicas de cenários de uso e ocupação do solo na bacia drenada pelo alto vale do rio Marrecas (PR) - Aguiar, Wagner de (2017)
Changes in soil use and occupation in watersheds affect the hydrological cycle, which may potentialize or delay the surface runoff of rainwater, as well as the impacts brought about by such process. This work aimed to understand the variation of the surface runoff of two main soil occupation conditions in the basin that drains the high valley of the Marrecas river, upstream of the urban perimeter of Francisco Beltrão-PR. The first condition evaluated the implications of the changes in the criteria for the delimitation of permanent preservation areas (PPAs) established by the new Forest Code (Law 12.651/2012), in detriment of the old standard (Law 4.771/1965), comparing them with the current use of the soil in the basin, in the process of flood mitigation. The second condition studied the temporal distribution generation potentials of surface runoff and the flood risks due to the seasonal dynamics of agricultural land use for each month of the year. The effects of surface runoff were verified by means of HEC-HMS simulated flow peaks, submitted to seven probabilities of precipitation occurrences. The changes in the Forest Code indicated a reduction of PPAs from 44.5 to 13.7%, resulting in a 22.1% increase in average flow peaks. Seasonal use of agricultural land temporarily delimited the months of April and March as the highest potential runoff generators, as well as the lowest in January and August, allowing the establishment of increase rates in the Marrecas river flow peaks due to the occupation of the soil in the contributing basin, ranging from 0.78 to 1.64 m3s-1 for each km2 of exposed soil, depending on the probability of precipitation. It is concluded that the institution of the new Forest Code, compared to the old one, reduced in 69.2% the recoverable PPAs, minimizing the legal possibilities of flood mitigation to the urban perimeter of Francisco Beltrão, as well as the seasonal use and agricultural occupation of the soil established a strong correlation between the increase in the flow peaks and the occupation by exposed soil.